Increased risk of colorectal cancer in type 2 diabetes is independent of diet quality. - Soghra Jarvandi; Nicholas O Davidson; Mario Schootman (PLoS ONE)
Background Poor diet increases the risk of both colorectal cancer and type 2 diabetes. We investigated the role of diet in the association between diabetes and colorectal cancer. Methods We analyzed data from 484,020 individuals, aged 50-71 years who participated in the prospective National Institutes of Health-AARP Diet and Health Study and were cancer free at baseline (1995-1996). History of diabetes was self-reported. Diet quality was measured with the Healthy Eating Index-2005 (HEI-2005), using a self-administered food-frequency questionnaire. Cox regression models were constructed to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of first primary incident colorectal cancer, overall and by anatomical location. Results During an average follow-up of 9.2 years, we identified 7,598 new cases of colorectal cancer. After controlling for non-dietary confounders, diabetes was associated with increased risk of colorectal cancer (HR 1.27, 95% CI: 1.18, 1.36). Further adjustment for diet quality did not attenuate this association. Diabetes was associated with a HR of 1.23 (95% CI: 1.07, 1.40) in individuals with good diet (quartile 4 of HEI-2005) and 1.58 (95% CI: 1.34, 1.86) in those with poor diet (quartile 1 of HEI-2005), compared to those with no diabetes and good diet. Moreover, diabetes was associated with a stronger risk of proximal than distal colon cancer (HR: 1.33 vs. HR: 1.20), while poor diet was associated with a weaker risk of proximal colon cancer (HR: 1.18 vs. HR: 1.46). Conclusion Diabetes and poor diet, independently and additively are associated with the increased risk of colorectal cancer.